2011
DOI: 10.1016/j.molcel.2011.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Suv39H1 by SirT1 Is Part of Oxidative Stress Response and Ensures Genome Protection

Abstract: Sirtuins are NAD-dependent deacetylases that sense oxidative stress conditions and promote a protective cellular response. The Sirtuin SirT1 is involved in facultative heterochromatin formation through an intimate functional relationship with the H3K9me3 methyltransferase Suv39h1, a chromatin organization protein. However, SirT1 also regulates Suv39h1-dependent constitutive heterochromatin (CH) through an unknown mechanism; interestingly, SirT1 does not significantly localize in these regions. Herein, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 35 publications
(55 reference statements)
8
123
2
Order By: Relevance
“…However, SIRT1 is able to reverse this modification and elevate SUV39H1 activity by facilitating the interaction between the SET domain and the post-SET domain of SUV39H1 (18). In addition, SIRT1 inhibits MDM2-mediated ubiquitination and the subsequent degradation of SUV39H1 during oxidative stress, which, in turn, increases the turnover of SUV39H1 in heterochromatin and protects genome stability (19). In comparison with the acetyl group or the ubiquitin molecule, the methyl group is neutral and relatively smaller; therefore, methylation may influence SUV39H1 by other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SIRT1 is able to reverse this modification and elevate SUV39H1 activity by facilitating the interaction between the SET domain and the post-SET domain of SUV39H1 (18). In addition, SIRT1 inhibits MDM2-mediated ubiquitination and the subsequent degradation of SUV39H1 during oxidative stress, which, in turn, increases the turnover of SUV39H1 in heterochromatin and protects genome stability (19). In comparison with the acetyl group or the ubiquitin molecule, the methyl group is neutral and relatively smaller; therefore, methylation may influence SUV39H1 by other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the phosphorylation of SUV39H1 during metaphase reinforces the association between SUV39H1 and the metaphase centromere (17). In addition, the deacetylation of SUV39H1 by silent mating type information regulation 2, homolog 1 (SIRT1) enhances SUV39H1 activity and facilitates heterochromatin formation (18), whereas the E3 ligase murine double minute 2, human homolog (MDM2)-mediated ubiquitination of SUV39H1 down-regulates SUV39H1 stability (19). Therefore, dissecting the potential PTMs of SUV39H1 in response to DNA damage may help us further understand the functions of SUV39H1.…”
mentioning
confidence: 99%
“…Microirradiation experiments and quantification of recruitment kinetics were performed following methods previously described (Hable et al , 2012) with some modifications. FRAP experiments were carried out as previously described (Bosch‐Presegue et al , 2011). …”
Section: Methodsmentioning
confidence: 99%
“…To further elucidate the role of Sirt7 on Sirt1, we wanted to explore whether Sirt7 also controls other Sirt1 effects on heterochromatin. Interestingly, in an overexpression system, we observed that Sirt7 co-immunoprecipitates with the histone methyltransferase Suv39h1 (Figure 1(A)), which is bound and activated by Sirt1 [20,22] suggesting formation of a tripartite Sirt7/Sirt1/Suv39h1 complex. Co-immunoprecipitation experiments in primary mouse embryonic fibroblasts (MEFs) confirmed that endogenous Sirt7 and Suv39h1 form a molecular complex (Figure 1(B)).…”
Section: Resultsmentioning
confidence: 99%